150 years of Darwin's theory of intercellular flow of hereditary information. Issue 12 (December 2018) - Liu, Yongsheng; Chen, Qi
In 1868, Charles Darwin published his Pangenesis theory, which proposed a mechanism for the flow of hereditary information between cells and generations. Pangenesis has since been disputed, but emerging evidence of cell-to-cell communication urges the reconsideration of this 150-year-old theory. Charles Darwin's Pangenesis theory, which proposed an intercellular mechanism for the flow of hereditary information, is gaining new ground.